Development Of Mobile Applications For Healthcare Consultation - Ratih Ayuninghemi; Atma Deharja (Prosiding International conference on Information Technology and Business (ICITB), 2017)
This paper discusses mobile applications developed as communication and consultation mediums between doctors and patients. E-Consul  has several features including a patient registration feature with a time limit to consult a physician, meaning that there is an expiry date on the account being used. For patients, they do not need to see a doctor in practice, but directly consulted bias when want to discuss related treatments. For doctors with this application the patient can not afford the time and distance to consult a doctor. Keywords : Mobile Application, Healthcare, and Consultation